Alcaloides ciclopeptídicos de Scutia buxifolia e suas atividades antimicrobianas - Marangon, Patrícia (2014)
The phytochemical investigation of the stem bark of the specie Scutia buxifolia (Rhamnaceae) led to the isolation of four cyclopeptide alkaloids: scutianine C (14) and three diastereoisomer of scutianine H (19), isolated and identified for the first time, coded as P06, P11 and P12 and called scutianines -N (37), -O (38) and -P (39), respectively. The metabolites had their structures elucidated on the basis of spectral data 1H and 13C NMR uni and bidimensional and high resolution mass spectrometry. The diasteroisomeric alkaloids P06, P11 and P12 had the stereochemistry of β-hydroxyamino acid (β-hidroxileucine) established from data 1H and 13C NMR by the coupling constants between H-3/H-4 and chemical shifts of C-3 and C-4. By NOESY technique spatial correlations of the hydrogens were verified and suggested stereochemical for phenylserine unit. The crude extract, the acidic and basic fractions and isolated compounds were tested as to their antimicrobial activity and all demonstrated antimicrobial potential.